(untitled) (Eurasian Medical Research Periodical, 2023)
Infections caused by COVID-19 have a high mortality rate in the world and mostly cause weakness in the respiratory system. The existence of several chronic diseases (comorbidities) along with COVID-19 infections causes the development and spread of these infections and increases the mortality rate. COPD is one of the diseases that increase the severity of COVID-19 infections.